The Twannberg iron meteorite strewn field in the Swiss Jura mountains: insights for Quaternary environmental conditions - Beda A. Hofmann; Naki Akçar; Sönke Szidat; Pierre G. Valla; Marcus Christl; Christoph Vockenhuber; the Twannberg Search Team (Swiss Journal of Geosciences, 2023)
Abstract The ~ 10 km2 strewn field of the Twannberg type IIG iron meteorite is located in the Swiss Jura Mountains, 30 km northwest of Bern. The strewn field has been mapped by a group of citizen scientists since 2006, yielding more than 2000 meteorite fragments with a total mass of 152.7 kg until the end of 2022. With a terrestrial age of 176 ± 19 ka and a minimum pre-atmospheric mass of ~ 250 t, the Twannberg meteorite is a local time marker in an area with a poorly-known paleoenvironmental history. The Twannberg strewn field is located just outside of the maximum extent of ice during the Last Glacial Maximum (LGM). On the Mont Sujet, meteorites are size-sorted in a 6-km long section of the primary strewn field (altitude 945–1370 m a.s.l.), indicating a fall direction from east-northeast to west-southwest (azimuth approximately 250°). On the Twannberg plateau and in the Twannbach gorge, meteorites are not size-sorted and occur in a ~ 5.7-km long area associated with till and recent stream sediments (altitude 430–1075 m a.s.l.). The mass distribution of meteorites on the Twannberg plateau demonstrate that these meteorites were not found where they fell but that they must have been transported up to several km by glacier ice flow after the fall. The distribution of meteorites and of glacially transported Alpine clasts on the Mont Sujet and on the Chasseral chain indicates the presence of local ice caps and of an approximately 200-m higher Alpine ice surface with respect to the LGM at the time of fall. This high ice level during MIS 6 (Marine Isotopic Stage 6, 191–130 ka) indicated by the meteorite distribution is consistent with surface exposure ages of 50–144 ka from nearby resting erratic boulders at altitudes of up to 1290 m a.s.l., including the newly dated Jobert boulder (63 ka). These boulders indicate an ice level ~ 400 m higher than during LGM at a time not later than MIS 6. Post-LGM luminescence ages of loess-containing meteorites on the Mont Sujet and 14C ages of materials associated with meteorite finds indicate relatively young pedoturbation and increased oxidation of meteorites since ~ 7300 cal BP, possibly correlated with deforestation and enhanced erosion resulting from increased human activities since the Neolithic. This study shows that Twannberg meteorites in their palaeoenvironmental context provide valuable information about ice levels and transport directions during MIS 6 and about their interaction with the post-LGM environmental conditions. The unique Twannberg strewn field has the potential to reveal more valuable information.